Case Report: Renal relapse after heart transplantation, induction, and autologous stem cell transplantation in a patient with AL amyloidosis with exclusive cardiac involvement - Puertas, Borja; Rey-Búa, Beatriz; Eiros, Rocío; Martín-Arribas, Alberto; Montero-Mateos, Enrique; Hernández-Sánchez, Alberto; Gómez-Úbeda, Sandra; Alejo-Alonso, Elena; Martín-López, Ana A.; Antúnez, Patricia; Villacorta-Argüelles, Eduardo; Gallego-Delgado, María; et al. (Frontiers in Hematology, 2022)
Currently, the daratumumab, cyclophosphamide, bortezomib and dexamethasone regimen is the standard of care for patients with AL amyloidosis. However, there is no consensus for treatment in patients with relapsed/refractory AL amyloidosis. Furthermore, there is no recommendation on what salvage therapy is optimal in the solid organ recipient with AL amyloidosis, such as a heart transplant. With this case we illustrate how treatment with daratumumab may be effective and safe in a patient with renal involvement at the relapse in a patient with AL amyloidosis after heart transplantation and autologous stem cell transplantation.